2018
DOI: 10.1002/hipo.23041
|View full text |Cite
|
Sign up to set email alerts
|

Differential responsivity of neurons in perirhinal cortex, lateral entorhinal cortex, and dentate gyrus during time‐bridging learning

Abstract: Many studies have focused on the function of hippocampal region CA1 as a critical site for associative memory, but much less is known about changes in the afferents to CA1. Here we report the activity of multiple single neurons from perirhinal and entorhinal cortex and from dentate gyrus during trace eyeblink conditioning as well as consolidated recall, and in pseudo‐conditioned control rabbits. We also report an analysis of theta activity filtered from the local field potential (LFP). Our results show early a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 97 publications
7
21
0
Order By: Relevance
“…Intrinsic firing activity in the LEC is very low (>1 Hz) and under trace learning conditions can increase to over 3 Hz (Suter et al, 2019). In anesthetized rats, resting activity in the range of 2–8 Hz has been detected in the DG (Dickson et al, 1994; Gloveli et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Intrinsic firing activity in the LEC is very low (>1 Hz) and under trace learning conditions can increase to over 3 Hz (Suter et al, 2019). In anesthetized rats, resting activity in the range of 2–8 Hz has been detected in the DG (Dickson et al, 1994; Gloveli et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Together, these results indicate that neonatal exposure to general anesthesia induces chronic changes to hippocampal microstructure which could contribute to the learning deficiency that was measured at the stage of adolescence. CA1 is considered to be a critical site for associative memory and neurons in DG participate in the processing of learning-related information 45 . It has been shown previously that miR-132, one of the microRNAs responsible for positive regulation of dendritic spines was downregulated at different time points (P14, P28, P60) after neonatal rats were exposed to propofol 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Suter et al (2019) discovered cells within dentate gyrus that showed changes in the firing rate that started at CS onset and persisted through the trace period during tEBC. This finding suggests that there are cells within DG that are bridging the temporal gap between stimuli, which would play a vital role in associative learning.…”
Section: Discussionmentioning
confidence: 99%
“…Neurogenesis in the adult brain occurs in the dentate gyrus (DG) and produces new neurons that mature into granule cells and integrate into existing circuitry (Altman and Das, 1965; Dayer et al, 2003). These highly excitable neural progenitor cells are believed to play a role in memory formation by providing enhanced plasticity to the hippocampus (Snyder et al, 2001; Mongiat et al, 2009; Suter et al, 2019). Indeed, there are some studies that have found that reducing the number of newborn neurons impairs memory acquisition on different associative memory tasks.…”
Section: Introductionmentioning
confidence: 99%